Improving the Finishing Process of Food Packaging Products Using DMAIC Method - Hery Hamdi Azwir (Universitas Katolik Parahyangan, 2022)
PT PP2 which is engaged in printing and packaging manufacturing has to provide good quality products and continue to make improvements to survive and win the competition. Currently, PT. PP2 produces a premium product which is a Food Packaging Product program from a company namely Target. Unfortunately, there were many defects found in the production area especially in the Finishing Process Section. Based on the historical data from August 2019, there were 184 pieces of defective products per shift. This study is conducted to reduce four main defects in the finishing process section of food packaging products which are Bending, Plastic Broken, Damaged Shrinkwrap, and PET Bumpy. The DMAIC methodology as a proven and well-known quality improvement method is selected for solving the problem escorting other methods or tools such as why-why analysis, brainstorming, Kaizen activities, and FMEA. The result of implementation shows that defects decreased by 9.05% (from 184 pieces to 21 pieces of defective products per shift) or from 10% down to 1.17%. With this achievement, PT PP2 can be meet the customer requirement and deliver the product within time. This study again also shows that DMAIC is one of the best choices in improving quality, especially in manufacturing industries.